Berlin Congress 1878 Through the Eyes of Phanariot Alexander Karateodori Pashi - R. Mihneva; V. Kolev (Vestnik MGIMO-Universiteta)
The article contributes to the historical literature on the Berlin Congress; it shows the events of the summer of 1878 through the eyes of the diplomats of the defeated Otto man Empire. The primary source for the article is the “Rapport” by the head of the Turkish delegation to the Сongress, Alexander Karathéodori Pasha (1833–1906), a Phanariote with Greek and Bulgarian roots, the son of the personal physician of Sultan Mahmud II and the first Ottoman lawyer. He graduated from the Sorbonne law faculty with a doctorate in law. Until recently, Turkish historians wrote about him more as a diplomat. However, in recent years, they started to pay attention to his extraordinary fate, the history of his family, in which there were many famous Phanariots. “Rapport” only in recent years began to attract the at tention of historians. The history of its creation is still unclear. It contains fascinating details of the relationship between representatives of a collective Europe at that time, the nature of their interests, and factors that outlined the fate of the Balkan region for decades to come. The report was written by Ottoman dignitaries when the Balkans finally became a “border area.” Its author noticed how the “big players” ’s geopolitical contradictions pushed the local people’s historical evolution along the “path” of future cataclysms. Alexander Karathéodori Pasha conveys, through seemingly minor details, the discord between the representatives of the “collective West” “and their desire to stop the attempts of the Ottoman Empire to follow the European paradigm of development. Against the background of the events in Berlin, Karathéodori eased the participants’ desires to start the quickest part of the “Ottoman inheritance” and drew attention to the beginning process of restructuring of international relations. He viewed the Berlin Congress analytically and realized its long-term implications.